Cover Picture: Nucleophilic Reactivity of a Nitride‐Bridged Diuranium(IV) Complex: CO2 and CS2 Functionalization (Angew. Chem. Int. Ed. 12/2016). Issue 12 (29th February 2016) - Falcone, Marta; Chatelain, Lucile; Mazzanti, Marinella
Abstract : The Venus flytrap … … is used to illustrate the importance of a framework built from siloxide ligands and a Cs + ion in capturing abundant CO2 and toxic CS2 under ambient conditions and in promoting their reactions with a bridging nitride in a diuranium(IV) complex. In their Communication onpage 4074 ff., M. Mazzanti et al. show how these processes lead to N−C bond formation and afford cyanate, thiocyanate, and unprecedented dicarbamate products.